IMPLEMENTASI STEGANOGRAFI PADA CITRA DIGITAL DAN KRIPTOGRAFI ALGORITMA HILL CHIPPER UNTUK PENGAMANAN INFORMASI BERUPA TEXT - Aldo Aldo; Lukman Hakim (Universitas Widyatama, 2018)
The exchange of information is very easy by using the internet as a liaison from the party who sends information to the party receiving the information. It is also easier for unauthorized parties to obtain information that will be sent from the sending party to the recipient via the internet. So that information requires security features. Encoding is a security technique to change information in the form of text, digital images, audio, video into information that has no meaning or is random. If the party who has the information that has been encoded does not have the key to open the encryption then the information cannot be read because it does not have a specific meaning. Insertion is a security feature wherein an information will be entered into a container media or the information is hidden in the container media. At this writing will be focused on creating a system that can encode, decrypt passwords, insert an information into a container media and extract information from a media that can be a digital image with the format: jpeg, bitmap, and png which is useful for increasing the level of security from an information. Encryption algorithm is an algorithm that converts an information (plain text) into a randomized information ( ciphertext) uses the specified key from the sender and recipient. The encoding algorithm used is the Hill Cipher algorithm. Which will be combined with the Least Significant Bit method as a method in the information insertion process. LSB will change every last bit value of each pixel in the cover image according to the binary value of the message in sequence, so that the result of the stego image will not change significantly if seen by the human eye.